Wearable Device for Athletes: An Approach to Individual and Collective Sports - Oliveira , Augusto C. R. de; Carvalho , Juliano Varella de; Bez, Marta Rosecler (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
Increasingly powerful and miniaturized mobile computing devices have been used in many areas and new possibilities of Internet of Things (IoT) have been created. In this context, there are wearable devices. They are characterized as intelligent devices, equipped with sensors sending signal to components, in the form of clothing or accessories, used near the user´s body. The sports area benefits with these devices, relating to data about the performance and health of the practitioners. The provision of this collected information is important, however, much of the devices collect and make available data individually, not allowing a macro view of groups and teams. The objective of this work is the construction of a prototype vest for the data capture of sportsman, together with an application able to evidence the information, meeting the demands of individual and collective sports, validating its relevance as an aid platform for decision making to health professionals and/or technical staff.